Effect of Vaccination Status on SARS-CoV-2 Antibody Levels in Gowa Regency Community, Indonesia - Mulyani Ilmy, A. Annisa; Ridwan,; Zulkifli, Andi; Arsin, A. Arsunan; Syam, Aminuddin; Seweng, Arifin (International Journal of Statistics in Medical Research, 2023)
Background: COVID-19 is a disease caused by infection with SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). One of the body's immune responses to infection is to produce antibodies. Acute SARS-CoV-2 infection initiates cellular and humoral immune responses. The humoral immune response specifically generates antibodies against virus-specific antigens. Several factors influence the immune response, one of which is vaccination status. Therefore, this study aimed to determine and analyze the effect of vaccination status on SARS-CoV-2 antibody levels. Methods: An analytical observational study with a cross-sectional design involving 815 samples was conducted. The proportional random sampling technique was employed based on data obtained from the Seroepidemiology Survey. Data analysis was conducted using the STATA version 14.0 program with the Independent T-Test, Mann Whitney test, Kruskal Wallis test, and Multiple logistic regression. Results: The results showed that there was a significant relationship between the determinant variables of SARS-CoV-2 antibody levels based on gender (p=0.012), vaccination status (p=0.000), and COVID-19 infection history (p=0.000). Furthermore, the multivariate analysis indicated that vaccination status was the variable most associated with SARS-CoV-2 antibody levels (p = 0.010). The OR value = 0.16 < 1 and 95%CI (0.04-0.65) which did not contain a value of 1 suggested vaccination status to be a significant protective factor associated with SARS-CoV-2 antibody levels, with a probability value of 94.1%. Conclusion: The most influential variable on SARS-CoV-2 antibody levels in the Gowa Regency was vaccination status. Moreover, none of the variables measured were identified as confounding factors or showed interaction effects.